Serum Levels of Irisin Predict Cumulative Clinical Outcomes in Heart Failure Patients With Type 2 Diabetes Mellitus - Berezin, Alexander A.; Lichtenauer, Michael; Boxhammer, Elke; Fushtey, Ivan M.; Berezin, Alexander E. (Frontiers in Physiology, 2022)
Background: The aim of this study was to investigate the role of serum irisin level in predicting clinical outcome in heart failure (HF) patients with type 2 diabetes mellitus (T2DM). Methods: 153 T2DM patients with HF aged 41 to 62 years were prospectively recruited for the study. Serum levels of irisin and NT-proBNP were measured by ELISA. Laboratory tests in-cluding HbA1c, fasting glucose, blood creatinine, insulin, lipids and creatinine with estimation of GFR were performed along with echocardiography at baseline. The observation period was 56 weeks. Results: We identified 76 composite cardiovascular (CV) outcomes, which included CV death and death from all causes, resuscitated cardiac death, non-fatal/fatal acute myocardial infarc-tion or stroke, and HF hospitalization. Therefore, the entire patient cohort was divided into 2 groups with (n = 76) and without (n = 77) composite CV outcomes. We found that the concen-trations of NT-proBNP were higher in HF patients with T2DM who had a CV composite out-come than in patients without CV composite outcome (P = 0.001). In contrast, the relationship was exactly reversed for irisin, as HF and T2DM patients with CV composite outcome had sig-nificantly lower irisin levels (P = 0.001). Unadjusted multivariate Cox regression analyses showed that LVEF < 40%, LAVI > 39 mL/m2, NT-proBNP > 2250 pmol/mL, and irisin < 6.50 ng/mL were the strongest predictors of CV outcomes in HF patients with T2DM. After adjust-ment for LVEF, serum levels of NT-proBNP and irisin remained independent predictors of end points. Furthermore, divergence of Kaplan-Meier curves pointed out that patients with NT-proBNP ≤ 2250 pmol/mL and irisin ≥ 6.50 ng/mL had a better prognosis than those with NT-proBNP > 2250 pmol/mL and irisin < 6.50 ng/mL. Conclusion: Adding irisin to NT-proBNP significantly improved discriminative value of the whole model. HF patients with T2DM had significantly better clinical outcomes when showing the constellation NT-proBNP ≤ 2250 pmol/mL and irisin > 6.50 ng/mL, respectively, in com-parison to patients with opposite trends for both biomarkers.